The effect of different foot and hand set-up positions on backstroke start performance - de Jesus, Ka.; de Jesus, Ke.; Abraldes, J. A.; Mourão, L.; Borgonovo-Santos, M.; Medeiros, A. I. A.; Gonçalves, P.; Chainok, P.; Fernandes, R. J.; Vaz, M. A. P.; Vilas-Boas, J. P. (Sports Biomechanics, 2016)
Foot and hand set-up position effects were analysed on backstroke start performance. Ten swimmers randomly completed 27 starts grouped in trials (n = 3) of each variation, changing foot (totally immersed, partially and totally emerged) and hand (lowest, highest horizontal and vertical) positioning. Fifteen cameras recorded kinematics, and four force plates collected hands and feet kinetics. Standardised mean difference and 95% confidence intervals were used. Variations with feet immersed have shown lower vertical centre of mass (CM) set-up position (0.16 m), vertical impulse exerted at the hands, horizontal and vertical impulse exerted at the feet (0.28, 0.41, 0.16 N/BW.s, respectively) than feet emerged with hands horizontal and vertically positioned. Most variations with feet partially emerged exhibited higher and lesser vertical impulse exerted at hands than feet immersed and emerged (e.g. vertical handgrip, 0.13, 0.15 N/BW.s, respectively). Variation with feet emerged and hands on the lowest horizontal handgrip depicted shorter horizontal (0.23, 0.26 m) and vertical CM positioning at flight (0.16, 0.15 m) than the highest horizontal and vertical handgrip, respectively. Start variations have not affected 15-m time. Variations with feet partially or totally emerged depicted advantages, but focusing on the entry and underwater biomechanics is relevant for a shorter start time.